Bringing Power Home: Exploring Community-Owned Energy Possibilities in Salem, Massachusetts - Lepler, Cole M.; Kenyon, Deanna R.; Manzo Gonzalez, Denisse; Jobin-Davis, Eliza H.; Garrido, Marina; Arent, Will P. (Tufts University Tisch Library, 2025)
2025 M.A./M.S. in Urban and Environmental Policy and Planning Field Project.; Project Partner: Salem Alliance for the Environment.